Oribatid mites of the genus Papillacarus Kunst 1959 (Acari: Oribatida) in Vietnam - Manh, Vu Quang (Academia Journal of Biology, 2012)
An outline of classification and identification key for 4 genera of the family Lohmanniidae Berlese 1916: Lohmannia Michael, 1898; Papillacarus Kunst, 1959; Javacarus Balogh, 1961 and Mixacarus Balogh, 1961; and the one for 3 species of the genus Papillacarus Kunst, 1959, recorded in fauna of Vietnam are given in the paper. According to the classification of Balogh J. and P. Balogh (1992), in the oribatid fauna of Vietnam there have been recorded 3 species from the genus Papillacarus Kunst 1959, as following: 1. Papilacarus aciculatus (Berlese, 1905) Biology and ecology: Living in soil surface layer of 0-20 cm; in agricultural field of polyannual and annual plants; in alluvial soil of the Red River system (FAO-UNESCO-WRB: Eutric fluvisol) and at 0-50 m above the sea level. 2. Papilacarus arboriseta Vu et Jeleva, 1987 Biology and ecology: Living in forest litter and substance laying 0-100 cm above soil surface and in soil surface layer of 0-20 cm; in natural and human-impacted forest, scrubland and grassland; in reddish brown soil derived from magmatic rocks, in brownish red soils derived from limestone’s (FAO-UNESCO-WRB: Gleyic aluvisols) and in reddish yellow humus soil in mountain (FAO-UNESCO-WRB: Humic acrisol); and at elevation of 400-1500 m above the sea level. 3. Papilacarus undrirostrarus Aoki, 1964 Biology and ecology: Living in soil surface layer of 0-20 cm; in garden surrounding habitation; in reddish yellow humus soil in mountain (FAO-UNESCO-WRB: Humic acrisol) and at elevation of 700-900 m above the sea level.